Effects of two weekly Gemcitabine in advanced stage head and neck cancers - Ateeqa Qayyum; Kashif Ali Sarwar; Sana Ahmed Khan; Zainab Shahzadi; Rabia Tariq (Medical Journal of South Punjab, 2024)
Objective: to assess the efficacy and toxicity of Gemcitabine in patients of Nasopharyngeal Carcinoma. Methodology: Prospective co-relational study was conducted at CMH Rawalpindi from February 2020 to February 2022 (period of 2 years). A total of 29 patients of nasopharyngeal carcinoma stage three and four were studied in the study. Three cycles of Injection gemcitabine were given at a dose of 1000 mg/m2 on Day 1 and Day 8 of chemotherapy along with injection cisplatin 60 mg/m2 on Day 1 in 3 weekly cycles. After three cycles all the patients were planned for Concurrent chemoradiotherapy to the local tumor sites and regional lymph nodes. All demographic, laboratory and clinical parameters were noted. Primary end point was overall survival and progression. Secondary end points were adverse effects experienced due to treatment. Results: Mean age of patients was 53.14 ± 10.98 years. Survival was better in stage 3 patients as compared to stage 4 patients. Most common side effect was anemia at 62.1% of the patients experiencing it. Oral ulcers were only seen on 9 (31%) of patients. Conclusion: This study illustrates that combination chemotherapy with cisplatin and Gemcitabine was beneficial in terms of disease progression and recurrence.